2021
DOI: 10.7861/fhj.2020-0193
|View full text |Cite
|
Sign up to set email alerts
|

The psychological impact of COVID-19 on healthcare workers in Pakistan

Abstract: IntroductionThe COVID-19 pandemic has challenged healthcare facilities and healthcare professionals' stamina and wellbeing. This study examines the psychological impact of COVID-19 on healthcare professionals. MethodsThis analytical cross-sectional study was conducted in July 2020 after institutional review board approval at a tertiary care institution in Lahore, Pakistan. A total of 175 healthcare workers participated following an online Depression, Anxiety and Stress Scale-21 (DASS-21) questionnaire invitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…This study showed that high levels of fear of COVID-19 were powerfully associated with negative emotional responses such as anxiety, depression, and stress. Furthermore, this study suggested that there was an urgent need for effective mental health training and counseling programs to promote mental health and diminish the chronic effects of COVID-19 pandemic (Riaz et al, 2021). A recent study revealed that a fear of COVID-19 had a substantial progressive association with emotional distress (anxiety, depression, and stress; Bakioglu et al, 2020).…”
Section: Discussionmentioning
confidence: 93%
“…This study showed that high levels of fear of COVID-19 were powerfully associated with negative emotional responses such as anxiety, depression, and stress. Furthermore, this study suggested that there was an urgent need for effective mental health training and counseling programs to promote mental health and diminish the chronic effects of COVID-19 pandemic (Riaz et al, 2021). A recent study revealed that a fear of COVID-19 had a substantial progressive association with emotional distress (anxiety, depression, and stress; Bakioglu et al, 2020).…”
Section: Discussionmentioning
confidence: 93%
“…The percentage of healthcare workers with moderate to severe anxiety was 30.3% without any association with factors such as gender, profession, salary, or direct contact with COVID-19 patients in healthcare settings. Studies conducted on healthcare workers from Pakistan [ 22 - 23 ] have consistently shown a higher percentage of study subjects suffering from anxiety when compared to an estimated prevalence of 23% reported in a systematic review of 12 studies conducted on more than 33 thousand healthcare workers from other Asian countries [ 24 ]. It is to be noted, however, that the majority of data for this systematic review was collected from studies conducted in China and Singapore, countries with a significantly higher GDP than Pakistan, therefore economic factors cannot be excluded when it comes to explaining a 30% increase in symptoms of moderate to severe anxiety amongst healthcare workers from Pakistan.…”
Section: Discussionmentioning
confidence: 99%
“…They should be provided with mental health resource and support when needed. [9,23] Organizations should promote self-care in nurses by offering flexible or shorter work hours, provide adequate breaks and more personal or vacation paid time off (PTO). [12] In one study, the building of resilience in healthcare workers during the COVID-19 was found to preserve their mental and psychological health and well-being.…”
Section: Discussionmentioning
confidence: 99%